1992
DOI: 10.1093/rheumatology/31.2.117
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Adrenal Infarction, Hypoadrenalism and Splinter Haemorrhages in the ‘Primary’ Antiphospholipid Syndrome

Abstract: We describe a patient with a 3-year history of recurrent deep vein thromboses (DVT) of the lower limbs, who developed adrenal insufficiency following withdrawal of warfarin therapy. Multiple splinter haemorrhages of the nail beds were evident, simultaneous with the development of adrenal infarction in the absence of infective endocarditis. CT scans of the adrenal glands were consistent with bilateral adrenal infarctions. The patient had persistently high titres of IgG anticardiolipin antibodies (aCL) over the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Ames et al have reported the case of a patient with PAPS who developed AI with adrenal failure following the withdrawal of warfarin therapy (17).…”
Section: Discussionmentioning
confidence: 99%
“…Ames et al have reported the case of a patient with PAPS who developed AI with adrenal failure following the withdrawal of warfarin therapy (17).…”
Section: Discussionmentioning
confidence: 99%
“…Like lupus anticoagulants, anticardiolipin antibodies were initially described in systemic lupus erythematosus, but now both have also been demonstrated in patients with other autoimmune disorders, in association with drugs and infection [6, 7, 8, 9, 10]. However, many patients with antiphospholipid antibodies have no other underlying disease [1, 2, 4, 11, 12, 13, 14, 15, 16]. Pelkonen et al [3]described deep vein thrombosis associated with lupus anticoagulant and anticardiolipin antibodies in 3 children.…”
Section: Discussionmentioning
confidence: 99%
“…In 1989, we first noticed an association of primary antiphospholipid syndrome and Addison’s disease in a patient with a history of deep vein thrombosis who developed acute adrenal gland insufficiency [2]. Ames et al [13]reported a patient with a history of deep vein thrombosis who developed acute adrenal insufficiency following withdrawal of warfarin therapy. The CT scans of their patient were thought of show swollen edematous adrenal glands with partial resolution occurring after 4 months, compatible with a previous acute infarction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was almost exclusively a postmortem diagnosis before computed tomography (CT) scan was developed. Anecdotal cases of survival have recently been reported in patients with bilateral adrenal hemorrhage associated with the antiphospholipid syndrome (7,8). We describe a new observation of definitive adrenal insufficiency caused by bilateral adrenal hemorrhage in a woman with a primary antiphospholipid syndrome.…”
mentioning
confidence: 99%